Find the sum of the given polynomials.ax + by + c, 2ax - 3by + c, and by - c

3ax - by + c
3a + x - bc
3ax + by - cd
bx - 3bc + a

Answers

Answer 1
Answer:   ax +  by + c
2ax - 3by + c
            by - c   
3ax - by + c   First Option.

You must align like terms before adding them. This is to ensure that there will be no confusion in getting the sum of the given polynomials.
Answer 2
Answer: If you would like to find the sum of the given polynomials, you can do this using the following steps:

ax + by + c + 2ax - 3by + c + by - c = ax + 2ax + by - 3by + by + c + c - c = 3ax - by + c

The correct result would be 3ax - by + c.

Related Questions

What type of solution does this equation have? *3x + 7 = 3x - 2no solutionone solutionInfinite many solutions
Factor 12y+6 using the gcf
Write the equation in fully simplified slope intercept form​
Which of the following is the scaling factor a of the function f(x)=3|x|?A. -1B. -3C. 1D. 3
Triangle inequality theorem-are the lengths 7, 4, and 2 of a triangle possible?

The inequality of 8z+3-2z<51 is

Answers

8z - 2z < 48
6z < 48
z < 8

Simplify the expression

Answers

the answer is option c

Answer: A

Step-by-step explanation:

Paula bought a ski jacket on sale for 6 less than half its original price. She paid 88 for the jacket. what was the original price?

Answers

88+6=94 This is half the original price. 94 times 2= 188

Answer:

The original price was $188

Step-by-step explanation:

URGENT!!!!! I NEED HELP AYUDA

Answers

4 sorry if I’m wrong

Solve the following inequality: 5x + 3 < 6x + 2

Answers

The sum of two numbers is 24 and the quotient is three. what are the two numbers?

Answers

a + b = 24...a = 24 - b
a/b = 3

(24 - b) / b = 3...multiply both sides by b
(24 - b) = 3b
24 = 3b + b
24 = 4b
24/4 = b
6 = b

a + b = 24
a + 6 = 24
a = 24 - 6
a = 18

so ur numbers are 18 and 6